019 Autologous stem cell transplantation versus alemtuzumab or ocrelizumab in relapsing remitting multiple sclerosis (StarMS). Issue 6 (27th May 2022) - Sharrack, Basil; Snowden, John; Muraro, Paolo
Abstract : In recent years, autologous haematopoietic stem cell transplantation (aHSCT) has been increasingly used to treat patients with highly-active relapsing remitting multiple sclerosis (RRMS). Observational and limited clinical trial data suggest that aHSCT reduces relapse rates, improves disability and enhances quality of life to a greater degree than most disease modifying therapies (DMTs). There is now a need to compare aHSCT with the two most efficacious DMTs: Alemtuzumab and Ocrelizumab. StarMS aims to determine whether aHSCT has superior clinical efficacy to Alemtuzumab and Ocreli- zumab with an acceptable safety profile. Mechanistic studies will assess immune re-constitution which will enhance understanding of the biological mechanisms of these treatments. Other sub-studies will assess their effect on cognitive recovery, neurofilament light and retinal nerve fibre layer measurements as markers of neuronal damage, and the safety of re-vaccination post-aHSCT. This EME funded parallel-group rater-blinded RCT will randomise 198 patients (1:1) to aHSCT versus DMT (Alemtuzumab or Ocrelizumab) from 19 centres across the UK. The primary endpoint, NEDA rate, will be assessed throughout the 2-year follow-up period. The StarMS trial has the potential to provide definitive data on the comparative efficacy of aHSCT vs highly efficacious DMTs, help improve patient outcomes, and impact national and international guidelines. basil.sharrack@nhs.net